2019
DOI: 10.1111/pirs.12374
|View full text |Cite
|
Sign up to set email alerts
|

The determinants of elderly migration in France

Abstract: The aim of this paper is to study elderly migration in France. First, it analyses whether the decision to migrate relies upon individual characteristics. Second, it examines the ways in which the economic, social and environmental characteristics of the French territories determine the retirees' choice of localization. The paper draws upon a unique database of 12.67 million French inhabitants, with information about their personal attributes and locational choices from 2003 to 2008. It also uses an original da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 63 publications
2
14
0
1
Order By: Relevance
“…Additionally, Sun‐belt Coastal District attracts elderly population by in‐migration as absolute change of elderly population in these settlements are positively affected by Sun‐belt Coastal District variable—in a sun‐belt settlement, in southwest Turkey, we expect an increase of 510 elderly on a five‐year period. This result is in line with the results obtained by similar studies, for example, Schaffar et al (2019). Specifically, effects of Sun‐belt Coastal District is interpreted to be more effective on life‐style in‐migration of elderly, associated with Activity Theory in addition to Disengagement Theory.…”
Section: Models Of Spatial Variation Of Elderly Population Distributi...supporting
confidence: 94%
See 2 more Smart Citations
“…Additionally, Sun‐belt Coastal District attracts elderly population by in‐migration as absolute change of elderly population in these settlements are positively affected by Sun‐belt Coastal District variable—in a sun‐belt settlement, in southwest Turkey, we expect an increase of 510 elderly on a five‐year period. This result is in line with the results obtained by similar studies, for example, Schaffar et al (2019). Specifically, effects of Sun‐belt Coastal District is interpreted to be more effective on life‐style in‐migration of elderly, associated with Activity Theory in addition to Disengagement Theory.…”
Section: Models Of Spatial Variation Of Elderly Population Distributi...supporting
confidence: 94%
“…Income may be a good indicator for relative attractiveness of a settlement. Other related studies also support use of income variable for elderly migration (Schaffar et al, 2019). Another locality variable is taken from indicators of well‐being index produced in 2015, that is, Health Satisfaction .…”
Section: Models Of Spatial Variation Of Elderly Population Distributi...mentioning
confidence: 74%
See 1 more Smart Citation
“…Studies conducted in France showed that factors such as location, cultural, and environmental amenities, a high quality of rendered public and private public services, and low crime rates mattered in seniors when taking decisions whether to migrate or not within a country and beyond it ( 28 ). The decisions connected with migration of seniors may be therefore derived from a combination of various factors, but one of the key motivators appears to be a comfortable access to medical care, where one of the determinants of which is the number of health care professionals acting on the market of health services, based on the data we used to conduct this analysis, as presented in the previous section.…”
Section: Discussionmentioning
confidence: 99%
“…Much of this literature focusses on location choices. It shows that senior households move to places with highly valued consumer amenities including health care, high temperatures and low taxes (Chen and Rosenthal 2008;Önder and Schlunk 2015;Dorfman and Mandich 2016;Graves and Waldman 1991;Kim 2011), closer to their place of birth (Schaffar et al 2018) or to their children (Bonnet et al 2010). As for housing choice, elderly seem to choose for a smaller dwelling size (Bian 2016; Eichholtz and Lindenthal 2014; Painter and Lee 2009), shared living (Engelhardt and Greenhalgh-Stanley 2010) and rental housing (Herbers et al 2014;Angelini and Laferrere 2012).…”
Section: Introductionmentioning
confidence: 99%